Early Pregnancy Loss in the 1st Trimester - David, Matthias; von Ahsen, Nicolas; Alkatout, Ibrahim; Bahlmann, Franz; Fehr, Peter Martin; Hancke, Katharina; Hiller, Ruth; Hodel, Markus; Hoopmann, Markus; Korell, Matthias; Manegold-Brauer, Gwendolin; Markfeld-Erol, Filiz; Müller, Annette M.; Oppelt, Peter; Rudnik-Schöneborn, Sabine; Sonntag, Barbara; Starkmuth, Susanne; Valet, Axel; Wallwiener, Stephanie; Weichert, Jan; Witzel, Simone; Becker, Sven (Geburtshilfe und Frauenheilkunde, 2025)
Purpose This guideline aims to improve and standardize the diagnostic and therapeutic approaches for different types of miscarriages, pregnancies of unclear localization, and ectopic pregnancies in the 1st trimester.Methods In accordance with the requirements for an S2k-guideline, this guideline was compiled following a search of the literature, and the various recommendations and statements were formally agreed upon by an interdisciplinary group of representative experts from Germany (DGGG, etc.), Austria (OEGGG) and Switzerland (SGGG) who met up several times under the aegis of the German Society for Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG).Recommendations The guideline provides 129 recommendations on clinical, laboratory-based, ultrasonographical, pathomorphological and genetic diagnostics and describes and assesses different therapeutic options in terms of their success and complication rates and the continued fertility of the patient as well as aspects of the grieving process and coming to terms with the loss after an early loss of pregnancy.Ziel Die Leitlinie soll zur weiteren Verbesserung und Vereinheitlichung des diagnostischen und therapeutischen Vorgehens bei Abortformen, Schwangerschaft unklarer Lokalisation und ektoper Gravidität im 1. Trimenon dienen.Methoden Entsprechend den Vorgaben für eine S2k-Leitlinie wurden die Inhalte basierend auf Literaturrecherchen in einer interdisziplinären, für das Leitlinienthema repräsentativen Gruppe aus Expertinnen und Experten aus Deutschland (DGGG u. a.), Österreich (OEGGG) und der Schweiz (SGGG) formal in mehreren Treffen unter Federführung der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG) konsentiert.Empfehlungen Es werden 129 Empfehlungen zur klinischen, laborchemischen, ultrasonografischen, pathomorphologischen und genetischen Diagnostik, Darstellung und Bewertung der verschiedenen therapeutischen Möglichkeiten bezüglich Erfolgs- bzw. Komplikationsrate und der weiteren Fertilität sowie zu Aspekten des Trauer- und Verarbeitungsprozesses nach frühem Schwangerschaftsverlust gegeben.
Keywords: guideline; miscarriage; ectopic pregnancy; pregnancy of unknown localization